2005
DOI: 10.1002/hyp.5983
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall‐runoff models using artificial neural networks for ensemble streamflow prediction

Abstract: Abstract:Previous ensemble streamflow prediction (ESP) studies in Korea reported that modelling error significantly affects the accuracy of the ESP probabilistic winter and spring (i.e. dry season) forecasts, and thus suggested that improving the existing rainfall-runoff model, TANK, would be critical to obtaining more accurate probabilistic forecasts with ESP. This study used two types of artificial neural network (ANN), namely the single neural network (SNN) and the ensemble neural network (ENN), to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(65 citation statements)
references
References 28 publications
2
60
0
3
Order By: Relevance
“…Early stopping has been recognized as a good strategy for avoiding overfitting and optimizing the generalization performance of NN models in practice [52]. The main idea is to inspect the test error of a NN model on an independent set using a validation data set, so that when the validation data set error starts to increase the NN training is stopped to avoid overfitting.…”
Section: Individual Neural Networkmentioning
confidence: 99%
“…Early stopping has been recognized as a good strategy for avoiding overfitting and optimizing the generalization performance of NN models in practice [52]. The main idea is to inspect the test error of a NN model on an independent set using a validation data set, so that when the validation data set error starts to increase the NN training is stopped to avoid overfitting.…”
Section: Individual Neural Networkmentioning
confidence: 99%
“…An ensemble neural network (ENN) designed to monthly inflows forecasting was applied in Ref. [14] to prediction of inflows into the Daecheong Dam in Korea. The ENN combined the outputs of the members of a neural network employing the bagging method.…”
Section: Introductionmentioning
confidence: 99%
“…Besides reducing uncertainty in the variance by mimicking randomness [EFRON, TIBSHIRANI 1993], ANN B models are simpler and easier to use in addressing uncertainty in an operational setting compared to Bayesian approaches [ISUKAPALLI, GEOR-GOPOULOS 2001]. Several studies have shown ANN B models to outperform standard ANN models [ABRA-HART 2003;HAN et al 2007;JEONG, KIM 2005;JIA, CULVER 2006;SHARMA, TIWARI 2009;SRIVASTAV et al 2007;TIWARI, CHATTERJEE, 2010a]. Both ANN W and ANN B hybrid approaches can be combined to form a wavelet-bootstrap-ANN (ANN WB ) model with the potential ability to achieve greater accuracy and reliability in real time water demand forecasting.…”
Section: Introductionmentioning
confidence: 99%